Hypoxia inducible factor 1α contributes to regulation of autophagy in retinal detachment - Shelby, Shameka J. (Exp Eye Res, 2015)
Photoreceptor (PR) cells receive oxygen and nutritional support from the underlying retinal pigment epithelium (RPE). Retinal detachment results in PR hypoxia and their time-dependent death. Detachment also activates autophagy within the PR, which serves to reduce the rate of PR apoptosis. In this study, we test the hypothesis that autophagy activation in the PR results, at least in part, from the detachment-induced activation of hypoxia-inducible factors (HIF). Retina-RPE separation was created in Brown-Norway rats and C57BL/6J mice by injection of 1% hyaluronic acid into the subretinal space. Retinas were harvested and assayed for HIF protein levels. Cultured 661W photoreceptor cells were subjected to hypoxic conditions and assayed for induction of HIF and autophagy. The requirement of HIF-1α and HIF-2α in regulating photoreceptor autophagy was tested using siRNA in vitro and in vivo. We observed increased levels of HIF-1α and HIF-2α within 1 day post-detachment, as well as increased levels of BNIP3, a downstream target of HIF-1α that contributes to autophagy activation. Exposing 661W cells to hypoxia resulted in increased HIF-1α and HIF-2α levels and increase in conversion of LC3-I to LC3-II. Silencing of HIF-1α, but not HIF-2α, reduced the hypoxia-induced increase in LC3-II formation and increased cell death in 661W cells. Silencing of HIF-1α in rat retinas prevented the detachment-induced increase in BNIP3 and LC3-II, resulting in increased PR cell death. Our data support the hypothesis that HIF-1α, but not HIF-2α, serves as an early response signal to induce autophagy and reduce photoreceptor cell death.